GENESIS TANAH DI ATAS BATUAN INDUK ULTRAMAFIK SERTA KESESUAIAN LAHANNYA UNTUK KELAPA SAWIT DAN CENGKEH DI KECAMATAN LANGGIKIMA, KONAWE UTARA, SULAWESI TENGGARA - , M. TUFAILA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research aims to identify the role of soil forming factors, specific soil formation process, soil characteristics, and soil classification formed on the ultramafic bedrocks as well as the land suitability level for oil palm and clove. The amount of 17 soil profiles are described and taken the soil samples to be analyzed in terms of their physical, chemical, and mineralogical characteristics, such as : the distribution of soil fraction, bulk density (BD), particle density (PD), water content at pF 2.54 and 4.20, permeability, pH, EC, organic-C, total N, P, and K, available P, potential K, exchangeable K, Ca, Mg, Na, Al, and H, CEC, BS, free Fe, Al, and Si, amorphous Fe, Al, and Si, organic complex Fe, Al, and Si, sand mineralogical and clay. Samples are taken from ultramafic rock (harzburgite, serpentinite, and olivine websterite) to be analyzed in terms of: pH abrasion, particle density (PD), total Ca, Mg, Mn, P, K, Na, Fe, Al and Si, and mineralogical. The research concludes that harzburgite and serpentinite rocks indicate a more intensive weathering and advanced level of soil development than olivine websterite. Specific soil formation process on harzburgite and serpentinite is desilication-ferralization, while that on olivine websterite is desilicationferritization. The formed soils contains a very high (15.07-26.06%) free iron (Fed) and are dominated by geothite and magnetite clay minerals. Soils on slope gradient 0-15% are dominated by Rhodic Acrustox, Petroferric Haplustox, Aquic Acrustox, and Typic Acrustox, while soils on slope gradient > 15% are Oxic Haplustepts, Lithic Haplustepts, Rhodic Kanhaplustalfs, and Kanhaplic Haplustalfs. In addition, most of the land in Langgikima Sub District is not suitable for oil palm and clove. The appropriate land classifiable into marginally suitable level (S3) is 3,791.88 ha (13.62%) for oil palm and 11,879.90 ha (42.66%) for clove with limiting factors such as slope gradient, rooting media, nutrient retention, and available nutrient. Therefore, organic material treatment, fertilization, and soil conservation are necessary to be performed.